Digital Marketing to Competitive Advantages of MSMEs in Kasongan, Kajigelem, Bantul, Yogyakarta - Sri Kussujaniatun; Sujatmika Sujatmika; Anis Siti Hartati (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2022)
This study discusses how to use digital marketing in marketing Micro, Small Medium Enterprise (MSMEs) products in Kasongan, Bantul. Digital marketing is an alternative for small and medium-sized businesses with limited promotional budgets. The use of social media such as Facebook, Whatsapp, Twitter, Instagram, Website and Tiktok is an alternative that can be used to create brand awareness, engagement, sales and even loyalty. The purpose of this study is to determine the use of digital marketing strategies in 115 MSMEs spread across Kajigelem, which consists of four villages namely Kasongan, Jipangan, Gendeng, Lemahdadi villages which have digitalized and the implications for the competitive advantage of these MSMEs based on consumer perceptions. The research method used is a quantitative method with research samples from consumers from MSMEs in Kajigelem, which consists of Kasongan villages. The sampling technique used purposive sampling on 200 respondents with multiple regression analysis. Based on the results of the study, it can be concluded that digital marketing has implications for the competitive advantage of MSMEs in marketing their products by 61% while the remaining 39% is explained by other variables not examined in the study